Pregnancy and Tumour: The Parallels and Differences in Regulatory T Cells - Muralidhara, Prerana; Sood, Vanshika; Vinayak Ashok, Vishnu; Bansal, Kushagra (Frontiers in Immunology, 2022)
Immunological tolerance plays a critical role during pregnancy as semi-allogeneic fetus must be protected from immune responses during the gestational period. Regulatory T cells (Tregs), a subpopulation of CD4+ T cells that express transcription factor Foxp3, are central to the maintenance of immunological tolerance and prevention of autoimmunity. Tregs are also known to accumulate at placenta in uterus during pregnancy, and they confer immunological tolerance at maternal-fetal interface by controlling the immune responses against alloantigens. Thus, uterine Tregs help in maintaining an environment conducive for survival of the fetus during gestation, and low frequency or dysfunction of Tregs is associated with recurrent spontaneous abortions and other pregnancy-related complications such as preeclampsia. Interestingly, there are many parallels in the development of placenta and solid tumours, and the tumour microenvironment is considered to be somewhat similar to that at maternal-fetal interface. Moreover, Tregs play a largely similar role in tumour immunity as they do at placenta- they create a tolerogenic system and suppress the immune responses against the cells within tumour and at maternal-fetal interface. In this review, we discuss the role of Tregs in supporting the proper growth of the embryo during pregnancy. We also highlight the similarities and differences between Tregs at maternal-fetal interface and tumour Tregs, in an attempt to draw a comparison between their roles in these two physiologic and pathologic states.